Development Strategy for LS Music Studio Bandung - A. Kifail Ahyar; Meriza Hendri SIP (Journal Research of Social Science, Economics, and Management, 2026)
LS Music Studio Bandung has operated for seven years in the hilly area of Cimenyan and has established a strong reputation. This research aimed to formulate a business development strategy for LS Music Studio Bandung through the Design Thinking approach, Business Model Canvas, and Timmons Entrepreneurial Process, as well as to assess its financial feasibility. The study employed a descriptive-analytical qualitative method, with data collected through direct observation, in-depth interviews with the owner, sound engineers, and regular clients, as well as literature reviews. The collected data were analyzed using SWOT/TOWS analysis, the Business Model Canvas, and investment feasibility indicators, including Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, Profitability Index, and Net Profit Margin. The results formulated a business model transformation from one to seven revenue streams, with projected revenue increasing from IDR 982.97 million in the first year to IDR 3.61 billion in the fifth year (2026–2030), supported by a Capital Expenditure (CAPEX) investment of IDR 106 million through a combination of equity financing and Micro KUR financing. The feasibility analysis showed an NPV of IDR 5.34 billion, an IRR of 447.7%, a Payback Period of 3.7 months, and a Profitability Index of 51.37, with a Timmons Model evaluation score of 76.4%. The proposed business plan was considered feasible for implementation and provides practical contributions to transforming LS Music Studio Bandung into a sustainable creative music production hub.